ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI JERUK DI DESA BELOK SIDAN KECAMATAN PETANG KABUPATEN BADUNG - Pradana, I Made Adi; Karmini, Ni Luh (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 10 No 12 (2021): VOL 10 NO 12, DESEMBER 2021 [4563 - 5005], 2022)
This study aims to influence harvested area, labor, farming capital through production on the income of citrus farmers. This research was conducted in Belok Sidan Village, Petang District, Badung Regency. The population in this study were citrus farmers in Belok Sidan Village, Petang District, with a total of 630 people. a sample of 86 citrus farmers in Belok Sidan Village. The sampling method used in this study is purposive sampling. This study uses path analysis or path analysis techniques to estimate the relationship between variables. The results of the analysis show that harvested area, labor, and business capital directly have a positive effect on the production of citrus farmers in Belok Sidan Village. Harvested area, labor, business capital and production directly have a positive effect on the income of citrus farmers in Belok Sidan Village. Harvested area, labor, and business capital indirectly affect farmers' income through the production of citrus farmers in Belok Sidan Village.   Keywords: harvested area, labor, business capital, production, farmer's income